(untitled) (Analysis in Theory and Applications, 2023)
Based on the results of the boundedness of μ^b_Ω on L^p spaces, by using the theory of atomic decomposition of Hardy spaces, we obtain the boundedness of μ^b_Ω on Hardy spaces.